Analysis Of The Effect Of Inflation, Exchange Rate, BI Rate On Islamic Insurance In 2018-2022 - Faizah Ariestya Anam; Faizal Amir (Jurnal Ekonomi, 2024)
Takaful is the first sharia insurance in Indonesia, established in 1994 and growing very fast. According to AASI research, Indonesia's share of Islamic insurance increased by 51.89% from June 2021 to 11.55 trillion rupiah. Investments in Islamic insurance companies must comply with regulations set by the Ministry. To achieve the target investment return, the institution is inseparable from various external factors that affect macroeconomic indicators. This study aims to determine how Exchange Rate, BI Rate, and inflation will affect Sharia Insurance in 2018-2022. This research uses quantitative research methodology and secondary data collection techniques. The data used in this study are monthly data from each variable and use VECM Model. The research results obtained are: The stationarity test in this test is stationary in the First Difference, in the optimal lag test it is known that the 5th lag is selected, in the VAR stability test it is known that the model is stable and passes the stability test where the model module is below 1. Vector Error Correction Model (VECM) will be tested to determine its impact. The long-term relationship between variables is indicated by the cointegration test results. Therefore, it is imperative to conduct additional testing using VECM analysis. There are two variables that are highly significant in the long-term model, namely Exchange Rate, and Bi Rate, while none of them significantly affect the movement of Islamic Insurance in the short term.The contribution of this research is to provide an update on how macroeconomic variables affect Islamic insurance with, there has been no other research that conducts this research with the VECM model, so this research is the first research that explains how macroeconomic variables affect Islamic insurance with the VECM model.